Safeguarding the Best Interests of Children after Parental Divorce: An Islamic Family Law and Psychological Perspective - Muhammad Akbar; Fikri; Agus Muchsin; Sudirman; Saidah (IAIN Parepare, 2026)
Parental divorce often places children in a vulnerable position because the dissolution of marriage may disrupt the fulfilment of their legal, emotional, educational, and social rights. This study examines how the principle of the best interests of the child is implemented after parental divorce from the perspectives of Islamic family law and child psychology. It specifically investigates the forms of protection provided to children, the legal and psychological consequences of divorce, and the relevance of Islamic legal principles in safeguarding children’s welfare. The study employed qualitative field research with an empirical juridical approach. Data were collected through interviews with students affected by parental divorce, guidance and counselling teachers, homeroom teachers, and other relevant school personnel, supported by observation, documentation, statutory regulations, Islamic legal sources, and scholarly literature. The data were analysed descriptively through data reduction, classification, interpretation, and triangulation. The findings indicate that protection for children after parental divorce remains insufficient in several respects. Some children experienced reduced parental attention, limited financial support, disrupted caregiving arrangements, declining learning motivation, emotional distress, social withdrawal, and behavioural changes. In several cases, daily care was transferred to grandparents or other relatives, revealing a gap between formal custody arrangements and actual parental responsibility. From an Islamic family law perspective, divorce does not terminate parental obligations concerning hadanah, maintenance, education, affection, and moral guidance. These obligations are consistent with the objectives of maqāṣid al-sharī‘ah, particularly the protection of life, intellect, and lineage. The study concludes that safeguarding children after divorce requires more than formal custody decisions; it demands sustained parental involvement, psychological assistance, school-based counselling, family cooperation, and institutional supervision. Future research should examine post-divorce child protection across broader social settings and develop integrated legal and psychosocial intervention models.